Thursday
March 30, 2017

Post a New Question

Posted by on .

solve each identity algebraically

1)(1-tanx)/(1-cotx)=-tanx

2)(1+cotx)/(1+tanx)=cotx

  • math - ,

    my usual approach is to start with the "messy" side, and change everything to sines and cosines.

    LS
    =(1- sinx/cosx)/(1 - cosx/sinx)
    = (cosx-sinx)/cosx * (sinx)/ (sinx - cosx)
    = (-1)sinx/cosx
    = -tanx

    perform similar steps for the second one, bet you'll get it

  • math - ,

    I got (1- sinx/cosx)/(1 - cosx/sinx)
    but how did (1- sinx/cosx) turn to (cosx-sinx)/cosx?

  • math - ,

    nevermind, found out :) thanks

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question